Antioxidant Activity of Rosemary Oil and Olive Oil and its Impact on the Shelf Life of Fish Fillets - Zunaira Khan; Roheela Yasmeen; Huma Shafique; Sana Shahbaz (BioScientific Review, 2024)
Background. Microbial spoilage is causing losses to food production at a large scale. This research aims to use oil-based natural preservatives with excellent antioxidant and antimicrobial properties. It provides updated information regarding the protein, fats, ash, and moisture contents of fish fillets after preservation with rosemary and olive oils, with glycerin and gelatin powder-based nanoemulsions.Method. To check the effect of oil-based preservation, proximate analysis and antioxidant activity tests were performed. Statistical analysis was performed using one-way ANOVA.Result. The experimental groups showed significant (p < 0.05) differences in different parameters as compared to the control group.Conclusion. The study found that rosemary and olive oil-based nanoemulsions significantly improved the nutritive value of fish fillets and extended their shelf life due to their strong antioxidant and antimicrobial properties.